Analysis of dog and cat population submitted to vaccination campaigns against rabies in a small city from Brazil - Babboni, S. D.; Fornazari, F.; Gonzalez, G. K.; Victoria, C.; Modolo, J. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In many developing countries domestic dogs and cats are the most important transmitters of rabies to men. The annual vaccination constitutes an important preventive activity, and the knowledge of animal population profile can assist future prophylatic programs, not just for rabies but also for other infectious diseases and social problems involving dogs and cats. In most Brazilian cities there is no census that can provide these data. One alternative, although limited, is to collect information from the vaccination campaign itself, realized by the public service. The present study aimed to analyze: the number of vaccinated dogs and cats in a small Brazilian city; their sex and reproductive status; and evaluate if there was a decrease in vaccinated animals after two years without campaign. The study was realized in the city of Botucatu (22°53’09”S 48°26’42”W), São Paulo State, Brazil, which comprises an area of 1,482.87 km2, has a human population of approximately 127,370 hab. (last census, 2010), and its dog and cat population are estimated to be 29,197 and 7,542 animals, respectively (Pasteur Institute estimative,2010). Data from the campaigns of 2009 and 2012 were obtained from the records of the Environmental Vigilance Department of the city. The total of vaccinated animals in 2009 was 26,664 (23,755 dogs and 2,909 cats) and in 2012 was 23,584 (20,195 dogs and 3,389 cats). The profile of the vaccinated dog population was as follow: in 2009 – 12,284 females and 11,471 males; 3,966 castrated and 19,789 intact. In 2012 – 10,659 females and 9,563 males; 5,281 castrated and 14,914 intact. The profile of vaccinated cat population was as follow: in 2009 – 1,699 females and 1,192 males; 1,307 castrated and 1,602 intact. In 2012 – 1,907 females and 1482 males; 1,537 castrated and 1,852 intact. The number of females was higher than males for both species and years. The proportion of intact animals was also higher than castrated ones, especially for dogs. These facts shown that the population of dogs and cats submitted to vaccination against rabies has a high proportion of individuals able to breed. This pattern probably also occur in the population of unvaccinated animals. Towards these data, local authorities should be aware of the problematic involving uncontrolled and undesirable reproduction of these species, which involves not just rabies control, but also other aspects of public health. During the years 2010 and 2011 there was no vaccination campaign against rabies in Botucatu. Nevertheless, only a small decrease in the number of vaccinated animals was observed in 2012. This difference is probably not significant, and can be observed among previous years with successive campaigns. Also, during 2012 there was no reinforcement in divulging the campaign against rabies. Thus, despite the two-year interruption of the vaccination campaign, the human population appears to continue to consider it as an important activity.